2014
DOI: 10.1055/s-0034-1373843
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends and Payer Differences in Lengths of Initial Hospitalization for Preterm Infants, Arkansas, 2004 to 2010

Abstract: Objective To examine the time trend in length of stay (LOS) and explore potential differences in neonatal LOS by insurance type for preterm infants in Arkansas between 2004 and 2010. Study Design There were 18,712 preterm infants included in our analyses. Accelerated failure time (AFT) models were used to model neonatal LOS as a function of insurance type and discharge year while adjusting for key maternal and infant characteristics, and complication/anomaly indicators. Results Prior to adjusting for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…1 The length-of-stay for preterm birth is also increasing at a pace of 0.59% each year, probably related to the survival of extremely immature infants. 2 The use of advanced technologies in the hospital has also influenced the increased use of technology post-discharge, especially with the capability to provide respiratory and renal support at home for small children. It is reported that infants with prolonged initial hospitalization may also be at risk for increased morbidity and mortality postdischarge.…”
Section: Introductionmentioning
confidence: 99%
“…1 The length-of-stay for preterm birth is also increasing at a pace of 0.59% each year, probably related to the survival of extremely immature infants. 2 The use of advanced technologies in the hospital has also influenced the increased use of technology post-discharge, especially with the capability to provide respiratory and renal support at home for small children. It is reported that infants with prolonged initial hospitalization may also be at risk for increased morbidity and mortality postdischarge.…”
Section: Introductionmentioning
confidence: 99%